2004
DOI: 10.1002/kpm.190
|View full text |Cite
|
Sign up to set email alerts
|

Global competition and the Australian biotechnology industry: developing a model of SMEs knowledge management strategies

Abstract: Approaches to the study of knowledge management (KM) strategies from within the management and information systems (IS) literature have traditionally relied on a resource-based view (RBV) of sources of competitive advantage. Recent studies on young, high-technology firms have highlighted that in practice these types of businesses also acquire competitive advantage through interfirm relationships involving knowledge sharing and strategies based on industry structure involving knowledge blocking. This research h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…KM principles have been studied and implemented in every organisational discipline and profession (Kebede, 2010). This diversity has contributed to the rapid advance of the field, but also to a lack of integration of ideas and terminology (Clarke & Turner, 2004). In this situation, there are several challenges to establishing KM as a separate discipline (Kebede, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KM principles have been studied and implemented in every organisational discipline and profession (Kebede, 2010). This diversity has contributed to the rapid advance of the field, but also to a lack of integration of ideas and terminology (Clarke & Turner, 2004). In this situation, there are several challenges to establishing KM as a separate discipline (Kebede, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Now that technologies implemented to enhance knowledge sharing have matured, researchers and practitioners are able to reflect on the factors of their success or failure (Hall & Goody, 2007). Besides, a divergence in the practioner's view on KM and the academic perspective is already evident (Clarke & Turner, 2004), and an increasing feeling of disappointment in managers due to their inability to foster organisational knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…2 80,81,82,83,84,85,86,87,88 . The task of organising and storing existing knowledge is enormous with minimal tangible benefits until the knowledge is reused.…”
Section: Knowledge Sharing Modelmentioning
confidence: 99%
“…Given that most biotechnology firms are downstream companies, it is clear that blocking patents and stacking licenses could well be a barrier against entry to the high-tech industry. In Australia, this issue of patent blocking is a significant issue to SMEs, particularly as non-Australian companies and institutions hold most of the biotechnology patents granted in Australia (Clarke and Turner, 2004). It is suggested that patents held by foreign companies, are for blocking purposes and will lie dormant.…”
Section: Approaches To Competitive Advantage Through Industry Structurementioning
confidence: 99%